How Far Could Someone Talk on Someone Else’s Religion (Case Study of Yahya Waloni) - Donandi S, Sujana (MIH FH UNSOED, 2025)
The problem in this article is: how far could someone speaking on the other religion believes in Indonesia? The study roles in giving identification on limitation for anyone who would to speak on the believes of other’s religion. The article is a Normative Legal Study discussed through a case study, by the case of Yahya Waloni who is accused for hate speech or blasphemy for claiming the bible is fake. The finding shows that anyone is free to talk on someone else’s religion with the content that is against the believes of the other religion, only as long as the one can prevent the speaking to be spread out to be accessed by the believers of the related religion. If the speaking is spread out, and the other religion believers consider it as an offense and blasphemy, then the speaker should be sentenced for the negligence to prevent the spread out. Keywords: Freedom of speech, Religion, Muhammad Yahya Waloni